An assessment of the levels of ethical perception among public University student in Malaysia - Low, Hock Heng (Universiti Teknologi Malaysia, 2003)
Ethics is indeed crucial because we will not survive the 21st century with the 20th century ethics. With the onset of globalization, many hands guide the controls and many decisions move those hands whose core values play an instrumental role in creating a stable and peaceful future for the world (Institute of Global Ethics, 1999).Denhardt (1999) suggests that ethics should be concerned with providing normative guidance, standards for behavior and goals for policy and practice at all levels.Colleges and universities are custodians of knowledge. Because possession of knowledge is the source of power, understood here as the ability to influence decisions in contemporary society, these institutions are also the gateway to power, significantly affecting the quality of economic and social life throughout the world. Thus, insofar as colleges and universities create and disseminate knowledge within a particular society,they are institutions with moral responsibilities to maintain the well being of that society (Wilcox and Ebbs, 1992). Ethics is not merely another subject or discipline taught at a university for the University is a community of scholars from a variety of disciplines who come together [uni-verto = turn into one because they are ultimately concerned with the common good of society, not merely the good of individuals (Curtin University, 2001). Today that concern extends to the ethical dilemmas currently faced by the global community.Thus, ethics should play a central role in a university and not merely a cosmetic role (i.e. as a set of rules to disciplinary misconduct). Education and training is the primary communications vehicle that a university can utilize to promote and instill core values so that students are able to recognize and respond to ethical dilemmas in personal, professional and global life. Globalization, liberalization and higher mobility made possible through Information and Communication Technology (ICT) revolution and the Internet amplify the role that the university play in producing individuals who can and will search within themselves to ensure that the power and responsibility bestowed upon them are factored into ethics i.e., Justice, Responsible Care and Respect for Persons.Students on today’s campuses encounter a variety of complex situations for which they are often ill prepared by experience or individual development. The relationship between students’ attitudes and values and the environment that supports or challenges them stands as a dynamic dialectic of confirmation and rejection that affects the ethical positions and choices of both the individual and the institution.Ethics can be defined as the rules and principles that define right and wrong conduct (Davis & Frederick, 1990). Whether an individual acts ethically or unethically is a result of complex interaction between the individual stage of moral development and several moderating variables including individual characteristics, organization structured design, organizational culture and the intensity of the ethical issues.